ANALISIS KEKERASAN SOSIAL DALAM NOVEL “KERLING SI JANDA” KARYA TAUFIQURRAHMAN AL-AZYZI - Erna Lesmana; Ayep Wahyudin; Eli Syarifah Aeni (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2019)
This study aims to (1) analyze the social violence contained in the novel "Kerling si Janda" by Taufiqurrahman Al-Azyzi. (2) to describe the forms of social violence contained in the novel. The method used in this research is descriptive qualitative. This method describes the state or a phenomenon that occurs. The author tries to dig and dissect the novel. This study was conducted by taking into account the aspect of dialogue between characters. Techniques of collecting data as follows; (1) read Intelligent “Kerling si Janda”, (2) analyze the forms of violence occurring in the novel, (3) write down fragments of sentences indicated by social violence and describe them. The results of the study show that in the novel “Kerling si Janda” by Taufiqurrahman Al-Azyzi is told a lot of social violence that occurred. The forms of social violence contained in the novel “Kerling si Janda” by Taufiqurrahman Al-Azyzi are manifested as verbal abuse, condescending words, vulgar comments, nicknames with negative connotations, threats, and screams.